THE USE OF ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH: PERSPECTIVES AND CHALLENGES - Abrudan, Cristina Laura (International Journal of Legal and Social Order, 2025)
Artificial Intelligence has become one of the most influential technologies of the 21st century significantly changing our lives, in different fields, such as business, education, and healthcare. The link between the technological development and education is obvious. The appearance of new technological changes has brought along also new challenges leading to a transformation of the teaching and learning process. Probably the most significant from all is the change from teacher-based education to student-centred education. New trends have appeared in the teaching and learning process of English due to the appearance of the Artificial Intelligence-based tools. The present study approaches the perspectives and challenges of teaching and learning English, focusing more on the students’ opinions regarding the introduction of AI-based tools in the teaching process. It is about the introduction of new technology as an everyday tool in the educational process. Do students consider AI-based tools effective in the learning process? Do they consider it useful? The study begins with a systematic literature review. Semi-structures interviews in the qualitative phase represent the instrument for data collection. The respondents have been 40 students, at different profiles, International Business in English – 10students; Accounting – 5 students; Marketing – 5 students; Tourism – 5 students; Finance-Banks – 10 students; Management – 5 students, at the Faculty of Economic Sciences, University of Oradea, being in the first and second year of bachelor studies. The results show that the intelligent content enhances the learning experience of the students, fostering interactivity and having a student-centred approach. The students perceive the integration of AI-based tools in the learning process have resulted in better outcomes due to its interactive and engaging character. The personalized experiences have also contributed to better results in the productive skills (speaking and writing) but also receptive skills (reading and listening). The significant integration of technology in what is known as blended learning has resulted in a boost in learning Business English, being more interactive, engaging and effective; it also contributes to the creation of personalized experiences that lead to an improved tailor-content based learning experience. The students feel that their skills (productive skills: speaking and writing and the receptive skills: reading and listening) have improved after a period of using technology- based tools in the teaching and learning process. The significant benefits come along with undeniable limitations. The challenges include: infrastructure requirements, aspects regarding inclusion and equity, the preparation and the readiness of the teacher, ethical aspects, data privacy and unequal accessibility. In the realm of education, the maximizing of the benefits of AI cannot be done without addressing these limitations. This research study can be continued with the teachers’ approach to the subject, the challenges and perspectives of teaching in the AI era.